Effect on Operating Parameters Towards Metastable Zone Width of Carbamazepine-Saccharin Co-Crystal - E. N., Engku Mat Nasir; Fatinah, Ab Rahman; S., Abd Rahim; Raihana Z., Edros; N., Anuar (2016)
Co-crystal is believed can improved physicochemical properties of an Active Pharmaceutical Ingredients (APis). Understanding in co-crystallization process is needed in order to have desirable crystal habits for materials. One of the studies that are important in designing co-crystallization process is kinetics study. In this research, carbamazepine (CBZ) and co-former saccharin (SAC) has been used to study the metastable zone width (MSZW) of the CBZ-SAC co-crystal in ethanol solution. The MSZW is studied by varying concentration of CBZ, mo) ratio values of SAC to CBZ and cooling rates used by polythermal method. Crystallization temperature and dissolution temperature is used to determine the maximum temperature difference ~Tmax using N)'vlt's equation.